Суб’єктивістські доповнення до законів попиту і пропозиції - Яковенко, Р. В.; Yakovenko, R.; Бідна, І. І.; Bidna, I. (Praha : Publishing House „Education and Science” s.r.o., 2011)
У тезах розкрито чинники попиту і пропозиції, що виходять за межі традиційного академічного аналізу Theses reveal the factors of demand and supply that go beyond traditional academic analysis
Subjectivist additions to the laws of supply and demand
Keywords: попит; ринковий механізм; пропозиція; лібералізація; задоволення; гранична корисність; demand; market mechanism; supply; liberalization; satisfaction; marginal utility